Poly(Methyl Methacrylate) as a matrix for immobilization of lipase - Yunus, W. M. Z. Wan; Salleh, A. B.; Ismail, A.; Ampon, K.; Razak, C. N. A.; Basri, M. (Humana Press, 1992)
Poly(methyl methacrylate) (PMMA) was found to be suitable for the immobilization of lipase from Candida rugosa. The best result based on hydrolytic activity was obtained by adsorption of the purified unbuffered enzyme solution onto PMMA beads without any modification of the beads. Prolonged exposure of the protein to the beads increased its adsorption but the expressed activity decreased after 1 h of exposure. The magnitude of the immobilized activity also varied with the size of the beads. Immobilization of the lipase shifted its optimal reaction temperature from 37 to 45°C. The immobilized enzyme is also more stable than the free enzyme in solution. The operational half-life of the immobilized lipase packed in a column and assayed in a closed system is 40 d.